2006
DOI: 10.1111/j.1540-8167.2006.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Clinical Application of Time‐Frequency Analysis of Atrial Fibrillation Electrocardiograms

Abstract: Fibrillatory waves of surface ECG lead V1 closely reflect right atrial, and, to a lesser degree, left atrial activity. Time-frequency analysis allows noninvasive monitoring of antiarrhythmic drug effects on fibrillatory rate and waveform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 35 publications
4
35
0
Order By: Relevance
“…16 Furthermore, the existence of an AA harmonic structure has been also associated to SR maintenance after internal 17 and external 27 ECV as well as in use of antiarrhythmic drugs. 31,32 Therefore, the agreement between these studies suggests that the harmonic structure of the surface AA signal could be a powerful outcome predictor of any AF treatment. In addition, given that a more organized AF has been associated with stronger harmonics in previous works, 27 it could be considered that patients with more organized fibrillatory activity present a higher probability to respond successfully to any treatment, including ablation.…”
Section: Main Findingsmentioning
confidence: 92%
See 2 more Smart Citations
“…16 Furthermore, the existence of an AA harmonic structure has been also associated to SR maintenance after internal 17 and external 27 ECV as well as in use of antiarrhythmic drugs. 31,32 Therefore, the agreement between these studies suggests that the harmonic structure of the surface AA signal could be a powerful outcome predictor of any AF treatment. In addition, given that a more organized AF has been associated with stronger harmonics in previous works, 27 it could be considered that patients with more organized fibrillatory activity present a higher probability to respond successfully to any treatment, including ablation.…”
Section: Main Findingsmentioning
confidence: 92%
“…Indeed, only some previous studies have tried to validate the surface DF with invasive recordings from different atrial regions, but reporting inconclusive results. 30,31,47 Anyway, all these works, regardless of the very dissimilar methodology employed, prove that the standard surface ECG can be considered as a promising tool for mean and long-term outcome prognosis of CA as well as for assisting the proper selection of patients undergoing this procedure.…”
Section: Previous Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, it can be speculated that with the currently available technology, localized intra-atrial phenomena such as micro-re-entry cannot be recorded on the surface. However, since frequency gradients between right and left atrial sites are dependent on the AF type (Lazar et al 2004), overall, there is also a good correlation of fibrillatory rates of left atrial sites and V1 (figure 5; Husser et al 2007b). Nevertheless, non-standard surface ECG lead positions such as at the posterior chest wall for better characterization of left atrial/pulmonary vein activity or identification of spatial variation have been validated in a preliminary study (Petrutiu et al 2006), and their feasibility for time-frequency analysis has been suggested (Husser et al 2007c).…”
Section: Clinical Applications (A ) Methods Validation and Reproducibimentioning
confidence: 93%
“…Previous works have shown that structural changes into surface f waves reflect the intraatrial activity organization variation [28,29]. Thus, it has been observed that ECGs acquired during intraatrial organized rhythms present f waves with well-defined and repetitive morphology and ECGs recorded during highly disorganized AA with fragmented activations contain surface f waves with very dissimilar morphologies [30].…”
Section: Surface Organization Assessmentmentioning
confidence: 99%